2009
DOI: 10.1007/978-3-540-92957-4_27
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Video Forgeries Based on Noise Characteristics

Abstract: Abstract. The recent development of video editing techniques enables us to create realistic synthesized videos. Therefore using video data as evidence in places such as a court of law requires a method to detect forged videos. In this paper we propose an approach to detect suspicious regions in video recorded from a static scene by using noise characteristics. The image signal contains irradiance-dependent noise where the relation between irradiance and noise depends on some parameters; they include inherent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Mean of intensities of each sub block is divided by mean of respective frame one by one as shown in (2). Hence for four different sub blocks of a particular frame, four new features are derived.…”
Section: Ratio For Each Sub Block: This Will Results In Four Identicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean of intensities of each sub block is divided by mean of respective frame one by one as shown in (2). Hence for four different sub blocks of a particular frame, four new features are derived.…”
Section: Ratio For Each Sub Block: This Will Results In Four Identicalmentioning
confidence: 99%
“…Kobayashi et al [2] proposed a powerful method to detect a duplicated region in the video based on noise characteristics. With the help of inherent parameters of a camera, result found was more accurate and reliable.…”
Section: Introductionmentioning
confidence: 99%
“…Passive approaches use internal features to detect if a video has been tampered in some ways. Some methods propose to use noise characteristics [5] to detect possible forgeries. Other works try to detect proofs of the evidence of a double compression [6,7].…”
Section: State Of the Artmentioning
confidence: 99%
“…In [20], the authors proposed another method that addressed the observation that a forged video will be recompressed, and the resulting artifacts due to the double quantization of coefficients can be used to detect forgery. In reference [5], the authors suggested a detection method for forged regions based on the inconsistencies of noise characteristics caused by the forged areas in different videos. A method based on accumulated differential images was proposed in [2], which used textural features to detect the forgery of moving objects removed from a static background.…”
Section: Introductionmentioning
confidence: 99%